Catalyst- and additive-free cascade phosphorylation/cyclization of propargylic alcohols and R2P(O)OH. (16th February 2021) - Zhang, Yuxing; Song, Xian-Rong; Jin, Fengyan; Yang, Tao; Yang, Ruchun; Xiao, Qiang
Graphical abstract: Highlights: Catalyst- and additive-free synthesis of 2 H -chromen-4-yl phosphinates/phosphonates. This reaction was achieved by cascade phosphorylation/cyclization of propargylic alcohols and R2 P(O)OH. This approach can be enlarged to gram scale. R2 P(O)OH acts not only as acid-promoter to initiate the reaction, and also as the phosphinate source. Abstract: A novel, catalyst- and additive-free cascade phosphorylation/cyclization of readily available 2-propynolphenols with R2 P(O)OH (R = aryl, OPh, OBn) was developed for the construction of 2 H -chromen-4-yl phosphinates/phosphonates and water as the only byproduct under mild conditions. The reaction was achieved by using R2 P(O)OH as acid-promoter, but also as the phosphinate source with the formation of phosphorylation allene intermediate, and followed by 6- endo -trig pathway. Additionally, this approach avoided the use of hazardous, air sensitive or activation reagents, and performed well with good functional group tolerance and satisfied yields.